Development of Minimum Competency Evaluation Instrument to Analyze Conceptual and Daily Life Abilities Based on The Rasch Model - Lutfi Amin, Muhammad; Supriyadi, Supriyadi; Susilaningsih, Endang (Journal of Research and Educational Research Evaluation, 2024)
Evaluating educational outcomes is crucial to ensuring that students develop both conceptual understanding and practical skills. However, existing evaluation methods often fail to comprehensively address both aspects. This study aims to fill this gap by developing a prototype evaluation instrument utilizing the Rasch Model to assess students' minimum competencies in conceptual understanding and real-life application. This research is developmental in nature. It includes content validity, reliability, and construct validity of the developed instrument. The study's respondents consist of 5 experts in the expert testing phase, 28 individuals in the small-scale test, and 132 individuals in the large-scale test. Data collection was conducted using both quantitative and qualitative approaches. The developed evaluation instrument provides a comprehensive assessment of minimum competencies in conceptual understanding and real-life application. The reliability tests include inter-rater reliability at 0.769, Cronbach's Alpha reliability for the small-scale test at 0.86 for single- point questions and 0.83 for four-point questions. The large-scale test results show a Cronbach's Alpha reliability of 0.87 for single-point questions and 0.83 for four-point questions. Based on the research findings and discussion, it can be concluded that the developed evaluation instrument for minimum competencies in conceptual understanding and real-life application demonstrates good validity and reliability. This study has the potential to significantly contribute to a more holistic evaluation of education.